Detailed Clinical and Histopathological Description of 8 Cases of Molecularly Defined CNS Neuroblastomas. Issue 1 (3rd December 2020) - Holsten, Till; Lubieniecki, Fabiana; Spohn, Michael; Mynarek, Martin; Bison, Brigitte; Löbel, Ulrike; Rutkowski, Stefan; Schüller, Ulrich
Abstract: Central nervous system neuroblastoma with FOXR2 activation (CNS NB FOXR2) has recently been described as a class of brain tumors sharing common genetic events and a highly similar DNA methylation profile. Most of these tumors have previously been diagnosed as primitive neuroectodermal tumor (PNET). Whereas the entity of PNET has been removed from the WHO classification of brain tumors in its current edition, CNS neuroblastoma was kept as an entity, but still lacks any molecular detail. Here, we describe 8 cases of CNS NB FOXR2 focusing on histomorphological and immunohistochemical features and include magnetic resonance imaging (MRI) for 2 of these cases. MRI revealed large supratentorial masses in superficial location with prominent cysts and necrosis, but little edema. Diffusion and enhancement characteristics were variable. Histological analyses showed that most of the cases displayed neuronal differentiation with necrosis, endothelial proliferation, and high vascularity. Immunohistochemistry revealed strong expression of synaptophysin, MAP2, and OLIG2 as well as moderate proliferation. These findings suggest that tumors with the molecular diagnosis of CNS NB FOXR2 may fit well into the WHO entity of CNS neuroblastoma. Our findings may be helpful when establishing an integrated diagnosis and may be indispensable if molecular data are unavailable.